The Expectations of Baby Moms and Toddlers in An Integrated Health Care (Posyandu) in Penggilingan Village East Jakarta - Eka Purnamawati; Novita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: This study explores the mothers' expectations of babies or toddlers towards Posyandu. Methods: A qualitative phenomenological study was conducted using in-depth interviews with 8 mothers (informants) from 5 Posyandu selected by simple random sampling. The study was conducted from Maret 2022. Explored concepts are structure, process, and output of expectation. The collected data was processed by coding and categorization Results:  Structural expectation combain 4 categories: accessbilities, human resources, facilities; the process issued 5 categories: service time, community volunteers/cadres, behaviour and communication, midwife/ healthworkes-mothers behavior/communication; and output included 3 categories: mother's desire to make babies and toddlers healthy, controlled growth and development of babies and toddlers, improving baby's quality of life and toddler. Conclusion:  The expectations of mothers with babies or toddlers towards Posyandu are formed from 3 components namely input, process and output.